2017
DOI: 10.1017/s0003055417000375
|View full text |Cite
|
Sign up to set email alerts
|

Ideology, Grandstanding, and Strategic Party Disloyalty in the British Parliament

Abstract: Strong party discipline is a core feature of Westminster parliamentary systems. Parties typically compel Members of Parliament (MPs) to support the party position regardless of MPs' individual preferences. Rebellion, however, does occur. Using an original dataset of MP votes and speeches in the British House of Commons from 1992 to 2015, coupled with new estimations of MPs' ideological positions within their party, we find evidence that MPs use rebellion to strategically differentiate themselves from their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 58 publications
1
65
1
1
Order By: Relevance
“…As a result, rebellious behaviour in the Labour party is now more likely to occur amongst centrist MPs than left-wingers (Slapin et al 2018). …”
Section: Discussionmentioning
confidence: 99%
“…As a result, rebellious behaviour in the Labour party is now more likely to occur amongst centrist MPs than left-wingers (Slapin et al 2018). …”
Section: Discussionmentioning
confidence: 99%
“…They also lend support to the notion that MPs use simpler language when they try to connect to constituents through their debate participation (Spirling ) and provide insight into how MPs use dissent and parliamentary speech to connect with voters (Kirkland and Slapin ; Slapin et al. ). As such, these findings contribute to our understanding of how MPs within parties use parliamentary behavior—rhetoric in particular—to distinguish themselves from fellow partisans, with potential implications for democratic representation.…”
mentioning
confidence: 72%
“…Indeed, recent literature has demonstrated that the individual MPs most likely to vote against their party are ideologically extreme members of the governing party (Slapin et al. ).…”
Section: Rebellion and Parliamentary Debatementioning
confidence: 99%
See 2 more Smart Citations